A new species of Dicnecidia Diakonoff (Lepidoptera: Tortricidae: Olethreutinae: Eucosmini) from Thailand and Laos - Pinkaew, Nantasak; Muadsub, Sopita; Jaikla, Soraya (Zootaxa, 2024)
Dicnecidia browni Pinkaew & Muadsub, sp. nov. is described from Thailand and Laos, representing the first records of the genus from these two countries. Illustrations of adults and genitalia are provided.